Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.18632/aging.100982
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor 6 derived from mesenchymal stem/stromal cells reduces age-related functional deterioration in multiple tissues

Abstract: The senescence-associated secretory phenotype (SASP) has attracted attention as a mechanism that connects cellular senescence to tissue dysfunction, and specific SASP factors have been identified as systemic pro-aging factors. However, little is known about the age-dependent changes in the secretory properties of stem cells. Young, but not old, mesenchymal stem/stromal cells (MSCs) are a well-known source of critical regenerative factors, but the identity of these factors remains elusive. In this study, we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 56 publications
4
26
0
Order By: Relevance
“…We also show decreased expression of the anti-inflammatory genes Foxo1 , Gdf6 , Igf1 , Igf2r , and Lpl (Ziouzenkova et al, 2003; Sukhanov et al, 2007; Savai et al, 2014; Hisamatsu et al, 2016). Lipoprotein lipase ( Lpl ), for example, is 14-fold lower in c-Kit deficient cells than in those isolated from littermate controls.…”
Section: Resultsmentioning
confidence: 72%
“…We also show decreased expression of the anti-inflammatory genes Foxo1 , Gdf6 , Igf1 , Igf2r , and Lpl (Ziouzenkova et al, 2003; Sukhanov et al, 2007; Savai et al, 2014; Hisamatsu et al, 2016). Lipoprotein lipase ( Lpl ), for example, is 14-fold lower in c-Kit deficient cells than in those isolated from littermate controls.…”
Section: Resultsmentioning
confidence: 72%
“…Meanwhile, IL‐1β and TNF‐α were both found to downregulate GDF5 expression significantly in human AF cells in 3D culture . In a mouse model, plasma levels of inflammatory factors were downregulated by overexpression of human GDF6 . This indicates an indirect role in the decrease of catabolic enzyme production linked to cellular response to proinflammatory cytokine signaling.…”
Section: Gdfs In Ivd Development Homeostasis and Potential For Regenmentioning
confidence: 92%
“…One growth factor recently proposed for NP regeneration is growth differentiation factor 6 (GDF6), a member of the bone morphogenetic protein (BMP) family that plays important developmental roles in the formation of cartilaginous tissues, including the IVD (Clendenning & Mortlock, 2012;Settle et al, 2003;Tassabehji et al, 2008;Wei et al, 2016). GDF6 expression has been linked to anti-ageing effects in multiple tissues (Hisamatsu, Ohno-Oishi, Nakamura, Mabuchi, & Naka-Kaneda, 2016) and, whereas studies conducted in our laboratory and others do not suggest GDF6 expression decreases with degeneration (Gulati, Chung, Wei, & Diwan, 2015; Le Maitre, Freemont, & Hoyland, 2009), preclinical studies have demonstrated that injection of GDF6 into experimentally induced rabbit and ovine annular puncture models attenuates pro-inflammatory molecular changes and prevents progression of IVD degeneration (Miyazaki et al, 2018;Shen et al, 2009). However, the hypocellular nature of the tissue and the aberrant phenotype of degenerate NP cells suggests that growth factor therapy alone may be insufficient to promote regeneration of human IVD.…”
Section: Introductionmentioning
confidence: 99%